Who Pays for the Minimum Wage? - Harasztosi, Peter; Lindner, Attila (American Economic Review, 2019)
This paper provides a comprehensive assessment of the margins along which firms responded to a large and persistent minimum wage increase in Hungary. We show that employment elasticities are negative but small even four years after the reform; that around 75 percent of the minimum wage increase was paid by consumers and 25 percent by firm owners; that firms responded to the minimum wage by substituting labor with capital; and that disemployment effects were greater in industries where passing the wage costs to consumers is more difficult. We estimate a model with monopolistic competition to explain these findings. (JEL J23, J24, J31, J38, L13)